Dianthus chinensis L.: The Structural Difference between Vascular Bundles in the Placenta and Ovary Wall Suggests Their Different Origin - Guo, Xue-Min; Yu, Ying-Ying; Bai, Lan; Gao, Rong-Fu (Frontiers in Plant Science, 2017)
Dianthus chinensis is a perennial herbaceous plant with great ornamental, botanical, ecological, and medicinal value. The pistil of D. chinensis is composed of two fused carpels with free central placentation and two separate styles. The placenta is a columnar structure extending about two-thirds the length of the maturing fruit, which is typical of the Caryophyllaceous. Traditionally, free central placentation is thought to have evolved from axial placentation by septal disappearance, and axial placentation to have occurred through fusion of conduplicate carpels with marginal placentation. However, the traditional doctrine is still taught in the classroom to explain the origin of carpels. To test the validity of this traditional theory, we performed an anatomical study of the pistil of D. chinensis. Our results indicate that its placenta has a vascular system independent of that of the ovary wall; that its ovules/seeds are attached to the placenta, which is a continuation of the floral axis enclosed by the lateral appendages, which constitute the ovary wall; and it has one or two amphicribral bundles in the center of placenta and numerous amphicribral bundles supplying the ovules/seeds in the pistil. The amphicribral vascular bundles supplying the ovules/seeds are comparable to those usually observed in branches, but not to those seen in leaves or their derivatives. This comparison indicates that the placenta in D. chinensis cannot be derived from the fusion of collateral vascular bundles of conduplicate carpels, as specified in traditional doctrine. Instead, the vascular organization in the placenta of D. chinensis suggests that the placenta is a shoot apex bearing ovules/seeds laterally. This conclusion is in line with the recently advanced Unifying Theory, in which the placenta is taken as an ovule-bearing branch independent of the ovary wall (carpel in the strict sense). Similar vascular organization has been observed in placentas of numerous isolated taxa other than D. chinensis. Whether such a pattern is applicable to other angiosperms is an interesting question awaiting an answer.